The Prevention of Revictimization of Female Victims of Sexual Violence in Higher Education - Ajrina, Alika Rahma; Kurniaty, Yulia; Hakim, Hary Abdul; Basri, Basri (Universitas Muhammadiyah Magelang, 2025)
This research aims to examine how the procedure for reviewing women victims of sexual violence in higher education so as not to experience revictimization. Issues related to sexual violence are a phenomenon that often occurs even in the educational environment, especially the Higher Education environment. The impact experienced by victims, especially by women who are victims of sexual violence, can be in the form of mental disorders, panic attacks, depression, dissociation, self-harm, post-traumatic stress disorder, and suicide, even during the examination. The research method used is normative empirical, with a statute approach and a case approach. The data source used in this research is secondary data consisting of primary and secondary legal materials. Then, the data is collected using a literature study (library research), then analyzed in a qualitative descriptive way. The discussion of this paper found that the examination of female victims of sexual violence in higher education has not been in line with the best interests of victims.